2021
DOI: 10.1155/2021/6653309
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Default-Mode Network Homogeneity in Melancholic and Nonmelancholic Major Depressive Disorder at Rest

Abstract: Background. Melancholic depression has been assumed as a severe type of major depressive disorder (MDD). We aimed to explore if there were some distinctive alterations in melancholic MDD and whether the alterations could be used to discriminate the melancholic MDD and nonmelancholic MDD. Methods. Thirty-one outpatients with melancholic MDD, thirty-three outpatients with nonmelancholic MDD, and thirty-two age- and gender-matched healthy controls were recruited. All participants were scanned by resting-state fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 66 publications
0
11
1
Order By: Relevance
“…In this study, we found that the PPD group showed increased DC in ORBinf.L that showed increased FC with the SFGmed.R, while decreased FC with the FFG.L compared with HCs. The medial superior frontal gyrus, as an important part of the superior prefrontal gyrus, is associated with self-consciousness, self-referential processing, emotion regulation, and cognitive processing ( Yan et al, 2021 ). It played a partial mediating role in the relationship between perceived stress and depression ( Wang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that the PPD group showed increased DC in ORBinf.L that showed increased FC with the SFGmed.R, while decreased FC with the FFG.L compared with HCs. The medial superior frontal gyrus, as an important part of the superior prefrontal gyrus, is associated with self-consciousness, self-referential processing, emotion regulation, and cognitive processing ( Yan et al, 2021 ). It played a partial mediating role in the relationship between perceived stress and depression ( Wang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has reported that the volume of the middle temporal gyrus (MTG) was strongly associated with deficits in language and reasoning ability, and both were the state-and traitrelated markers of depression (Ang et al, 2020). In our previous studies, we found that melancholic MDD showed lower NH in the bilateral MTG than HCs, especially in the right MTG/MTP (Cui et al, 2017;Yan et al, 2021). Decreased ReHo in the right MTG was also reported in remitted geriatric depression (Yuan et al, 2008).…”
Section: Discussionmentioning
confidence: 76%
“…NH is a new approach for detecting specific loci of compromised connectivity, and for studying within-network coherence. It has been used to study several diseases, such as attention deficit/hyperactivity disorder ( 39 ), major depressive disorder ( 54 , 55 ), schizophrenia ( 42 ) and mild cognitive impairment ( 56 ). We applied this method to estimate the DMN homogeneity in TLE at rest.…”
Section: Discussionmentioning
confidence: 99%